A escolaridade dos pais, os retornos à educaç\~ao no mercado de trabalho e a desigualdade de rendimentos - Lauro Ramos; Mauricio Reis (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper investigates the impact of parental education on the earnings returns to schooling and the consequences of this effect for income inequality in Brazil. The empirical analysis uses data from the 1996 Brazilian Household Survey (PNAD). According to the estimated results, each additional year of schooling is associated with an increase of 4.8% in the earnings differential between workers whose parents had at least 8 years of education and those workers whose parents did not complete 4 years of schooling. The results also indicate that earnings inequality would be reduced and the average labor earnings would be increased a lot if workers with low educated parents have the same return to schooling that those workers whose parents have achieved higher levels of education.
Keywords: J24; J31; 330